Study of contact resistivity of a no-insulation superconducting coil. (29th January 2021) - Liu, Yingzhen; Ou, Jing; Gyuraki, Roland; Schreiner, Fabian; de Sousa, Wescley T B; Noe, Mathias; Grilli, Francesco
Abstract: Previous studies of test coils have demonstrated the high thermal and electrical stability of no-insulation (NI) high temperature superconducting (HTS) coils thanks to the presence of turn-to-turn current paths. These turn-to-turn current paths in a NI coil are significantly influenced by the contact resistivity. In practice, it is very challenging to measure the contact resistivity of a NI coil by direct experiments of short samples, since the contact resistivity of superconducting tapes is influenced by surface roughness and tolerance, stress, temperature etc. A proper simulation model is needed to investigate the contact resistivity of the NI coils with dedicated experiments. Hence, in this paper a distributed circuit model is employed. This model, implemented in Matlab 2018a, considers the local contact resistivity, self and mutual inductance, and HTS resistance, which depends on the supplied current, magnetic field and temperature. To validate the model, experimental results from literature, including sudden discharge, and charge–discharge processes, are employed and the results from simulations are consistent with experimental results. Then the model is used to investigate the equivalent contact resistivity of a 157-turn NI coil. Through the comparison of simulated and experimental results, it is found that the contact resistivity of the NI coil has an inhomogeneous distribution. When the current changes with different speeds, ramping rates or frequency, a different number of turn-to-turn contacts carries radial current. Since the turn-to-turn contacts have different contact resistivity, the equivalent contact resistivity calculated from sudden discharge cannot be used in simulations to reproduce all the experimental data.